Report of the ILO Round Table for Caribbean Employers' Organisations, Grenada, 23-27 August, 1990: reference paper (ILO. PREALC Port of SpainTT, 1991)
Provides information on ILO projects for Caribbean employers in the area of management and small enterprise development. Discusses various wage reform/payment incentive systems as they have been applied in the region. The social implications of structural adjustment are also discussed. Summarizes the global structural changes which are affecting Caribbean economies. Outlines future activities for employers' organisations in the Caribbean.
DC